Physico-Chemical Evaluation of Honey Fortified with Oleaginous Seeds - Ariana Bianca Velciov; Adrian Riviş; Corina Iuliana Costescu; Georgeta Sofia Pintilie; Anca Maria Jidic (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2014)
This research followed to achieve some natural-fortified food, based on honey and oleaginous fruits. Honey and oleaginous fruits are extremely valuable for human diet. With their rich nutrient content, new products obtained by mixing honey with seeds may be considered both traditional food with high nutritional value as well as fortified food. The samples were constituted from acacia flowers honey bought directly from the producer, to which were added various quantities of oleaginous fruits (seeds). Thus, we obtained 3 different types of fortified honey, using pumpkin seeds, sunflower seeds and hemp seeds. Samples obtained were stored in appropriate conditions. From these samples, were made analytical tests: ascorbic acid and humidity.